2008
DOI: 10.1007/s00415-008-0050-4
|View full text |Cite
|
Sign up to set email alerts
|

Basal ganglia volume and clinical correlates in ‘preclinical’ Huntington’s disease

Abstract: In line with previous research we demonstrated that basal ganglia abnormalities precede overt disease manifestation of HD. Besides we showed that smaller basal ganglia volumes are related to subtle motor abnormalities and worse psychomotor performance in gene carriers without clinical diagnosis. Motor and psychomotor measures may be suitable clinical markers in future neuroprotective trials when combined with volumetric imaging.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
67
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(79 citation statements)
references
References 36 publications
10
67
1
Order By: Relevance
“…Kipps et al 10 suggest that cortical and white-matter atrophy may be more variable in location compared with the relatively concentrated striatal loss, making it more difficult to detect using voxel-based measurement techniques. The rate of globus pallidus atrophy was also significantly greater in the far and near groups than in the controls, consistent with cross-sectional reports of prodromal volume reduction in this area 22 23…”
Section: Discussionsupporting
confidence: 85%
“…Kipps et al 10 suggest that cortical and white-matter atrophy may be more variable in location compared with the relatively concentrated striatal loss, making it more difficult to detect using voxel-based measurement techniques. The rate of globus pallidus atrophy was also significantly greater in the far and near groups than in the controls, consistent with cross-sectional reports of prodromal volume reduction in this area 22 23…”
Section: Discussionsupporting
confidence: 85%
“…Pillai et al (2012) reported a mean score of 23.7 (15-28) for cognitive impairments assessed using the MMSE in the moderate stages of in the severe stages. However, our MMSE results were very similar to those of other studies for the range of 42-46 CAG expanded alleles (Reedeker et al, 2010;Jurgens et al, 2008;Oliva et al, 1993;Dorsey et al, 2013). The results obtained assessing the UHDRS varied more when individuals bearing 42-46 CAG repeats were compared (Jurgens et al, 2008;Vaccarino et al, 2011).…”
Section: Discussionsupporting
confidence: 91%
“…Unsurprisingly, a longer disease duration has been found to be associated with higher scores on the UHDRS motor assessment in most patients (Kirkwood et al, 2001). A longer disease duration is also related to worse MMSE scores (Jurgens et al, 2008;Reedeker et al, 2010). A high degree of internal consistency between the motor, behavioral, cognitive and functional components of the UHDRS is observed.…”
Section: Discussionmentioning
confidence: 99%
“…Putaminal metabolite changes are pertinent since this is a site of early atrophy, identifiable years prior to clinical diagnosis. 29 Furthermore, putaminal atrophy correlates with psychomotor and motor deficits in premanifest HD 30 and early HD. 31 Our correlations suggest a possible role for MRS in evaluating the ability of an intervention to slow disease progression.…”
Section: Huntington Disease (Hd)mentioning
confidence: 99%